Dopamine-related striatal neurophysiology is associated with specialization of frontostriatal reward circuitry through adolescence. (June 2021) - Parr, Ashley C.; Calabro, Finnegan; Larsen, Bart; Tervo-Clemmens, Brenden; Elliot, Samuel; Foran, Will; Olafsson, Valur; Luna, Beatriz
Highlights: Connectivity between the vmPFC - NAcc decreased through adolescence. Decreases in vmPFC - NAcc connectivity supported developmental improvements in reward-learning and decreases in risk-taking. NAcc tissue iron, reflecting dopamine-related striatal neurophysiology, mediated age-related decreases in connectivity. Changes in DA may play a role in specialization of frontostriatal circuitry, supporting decreased risk-taking in adulthood. Abstract: Characterizing developmental changes in frontostriatal circuitry is critical to understanding adolescent development and can clarify neurobiological mechanisms underlying increased reward sensitivity and risk-taking and the emergence of psychopathology during this period. However, the role of striatal neurobiology in the development of frontostriatal circuitry through human adolescence remains largely unknown. We examined background connectivity during a reward-guided decision-making task ("reward-state"), in addition to resting-state, and assessed the association between age-related changes in frontostriatal connectivity and age-related changes in reward learning and risk-taking through adolescence. Further, we examined the contribution of dopaminergic processes to changes in frontostriatal circuitry and decision-making using MR-based assessments of striatal tissue-iron as a correlate of dopamine-related neurobiology. Connectivity between the nucleus accumbens (NAcc) and ventral anterior cingulate, subgenual cingulate, and orbitofrontal cortices decreased through adolescence into adulthood, and decreases in reward-state connectivity were associated with improvements reward-guided decision-making as well as with decreases in risk-taking. Finally, NAcc tissue-iron mediated age-related changes and was associated with variability in connectivity, and developmental increases in NAcc R2' corresponded with developmental decreases in connectivity. Our results provide evidence that dopamine-related striatal properties contribute to the specialization of frontostriatal circuitry, potentially underlying changes in risk-taking and reward sensitivity into adulthood.